The Effect of Banana (Musa nana Lour.) Peel Extract and Omega-3 on Biochemical and Histopathological Characteritics in Rat Model of Polycystic Ovary Syndrome - Jamal Yazdani; Mohammad-Jafar Dehzad; Mohammad Mehdi Ommati; Reza Heidari; Mohammad Reza Arabnezhad; Najmeh Hejazi; Afsaneh Ahmadi (International Journal of Nutrition Sciences)
Background: In women of reproductive age, polycystic ovary syndrome (PCOS) is a prevalent endocrine condition. This study assessed the effect of banana (Musa nana Lour.) peel extract and omega-3 on biochemical and histopathological features in rat model of PCOS.Methods: After PCOS induction, 56 adult female rats were randomly divided into seven groups. In group 1, healthy rats were given 20 mg/kg/day of normal saline. Group 2 comprised PCOS rats receiving saline as 20 mg/kg/day. Group 3 included rats with PCOS receiving 240 mg/kg/day omega-3. Group 4 consisted of rats with PCOS receiving 6mL/kg/day of banana peel extract. Group 5 contained rats with PCOS receiving 12 mL/kg/day banana peel extract. Group 6 enrolled rats with PCOS taking 240 mg/kg/day omega-3 and 12 mL/kg/day banana peel extract. Group 7 consisted of rats with PCOS treated with 200 mg/kg/day metformin. Serum biochemical parameters and ovarian oxidative stress were evaluated together with histological assessment. The duration of treatment for all groups was 8 weeks.Results: Glycemic indices, serum triglyceride level, serum testosterone concentration, oxidative stress, and body weight significantly decreased. The ovarian tissue pathology in the animals treated with banana peel extract and omega-3 in comparison to the PCOS control group showed an improvement (p<0.05).Conclusion: Omega-3 supplementation with banana peel extract as an antioxidant may have beneficial effects on biochemical parameters and pathological demonstrations of PCOS.